ANALISIS ANTRIAN PADA PT. POS INDONESIA (PERSERO) CABANG SANGGATTA - Adi Suroso, Sherly Marlina, LCA. Robin Jonathan (EKONOMIA, 2015)
Problem formulation in this research is Is queuing system of double track and single service applied to the PT. Pos Indonesia (Persero) Branch Sangatta already efficient. The aim of this study was to analyze to determine the queuing system of double track and single service at Post Office branches Sengata if it runs efficiently and analyze the application of the theory of queuing at the Post Office branch SangattaUsed theoretical basis of this research is the Operational Management that includes the definition of management, the definition of Management Operations, Objectives and Functions ROP, and Queueing Theory. Queue System Hypothesis double track and single service at PT. Pos Indonesia (Persero) Branch Sangatta not efficient.The analysis tool in this research is the modeling formula proposed by T. Hani Handoko (2000: 5) which is used to 1). To calculate the level of usefulness of single services and facilities section doubles. 2). Calculating the level of utility services 3). Calculating the amount of the average - average in the queue 3) calculate the waiting time for customers 4). Calculate the average number in the queue.Research Associate Service process and a single lane, the level of busyness officer PT. Pos Indonesia (the Company) Branch Senggata is 40% means the clerk special letters have idle time 60% .artinya often occur no customers were queuing up, this is corroborated by the results of the calculation of the probability of the absence of a system to wait for 0.4347 or 43.47 %. Results of average calculation - average queue time is 0.1545 customers per day per hour of work, while the average - average wait to be served is 34 seconds using multiple queue system facilities and single track. From the above calculation, the value P = 0.4 When consulted by Criteria Testing Hypothesis which states that if p <1, then the use of the facilities Double with single track in serving customers has not been efficient, meaning hypothesis proposed in this study proved and accepted. The mean score in the queue at the counter special letter obtained values to Lq = 0.1545 When consulted by the criteria of hypothesis testing Lq> 0, then the average - average number of queues is not efficient, means the hypothesis is accepted. Similarly, the average - average wait to be served at the counter special letters Wg = 0.0096 value is greater than zero, this is when adjusted for hypothesis testing criteria Wq> 0, then the average - average waiting time in the queue is not efficient, meaning hypothesis be accepted